Can cyber communities support mental health help-seeking? A social capital perspective - Zhen Li; Yueling Xu; Hongxia Chen; Changtian Yang; Xiaofang Chen (Humanities and Social Sciences Communications, 2026)
Abstract Cyber communities serve as online platforms for college students, offering potential avenues for mental health help-seeking. This study applies the social capital theory framework to the help-seeking context and explores the impact of perceived integration on cyber community usage and the moderating role of stigma on help-seeking intentions. A total of 1242 college students from 7 universities in Zhejiang Province participated in the survey. The findings indicated that social interaction ties, norms of reciprocity, and shared values significantly influence college students’ help-seeking intentions but were not strongly correlated with reductions in stigma. Meanwhile, the empirical results revealed that perceived integration of online and offline use within the cyber community was beneficial for college students’ help-seeking intentions and for reducing stigma. This study contributes to the understanding of college students’ usage behaviour in cyber communities. It provides timely insights for government policymakers and school administrators to promote sustainable help-seeking practices in China and other countries.